The Theory and Economics of MARS and MOON Colonization: Steps and Policy Advocacy - M.B., Dastagiri (European Scientific Journal, ESJ, 2017)
World-renowned astrophysicist Stephen Hawking has said that humanity will face a choice between space colonization and extinction. NASA wants to put a human on an asteroid by 2025 and on Mars by 2030. Scientific discoveries solve global economic and interplanetary economic problems. Economics and Science are two important drivers for mankind welfare. The economic driver of man would pursue extraterrestrial life. New Economics deal the economic driver of industrialization of moon and colonization of mars. The present study focuses on the theory, economics, steps and possibilities of colonization of mars and moon in specific and other planets in general. The study is based on frame work of vision and the metaanalysis of history of intellectual Economics and inter planetary explorative space research. The study analyzes historical planetary space research evidences, insights and rationales on colonization of Mars, Moon and other planets and life possibilities and steps to achieve. It also analyzes the theory and New Economics that bridges economics opportunities and Inter planetary space colonization which is imperative for extraterrestrial life and prosperity. The study uses meta-analysis of inter planetary research which has done by NASA, Japan, UK, Germany, Russia, India, Netherlands and other countries. The study found that surface conditions and the presence of water on Mars make it the most hospitable of life. New studies suggest that Moon more hospitable to life. It was reported that some lichen and cyanobacteria survived. Mars’s north and south poles are attracted great interest as settlement sites. The ultimate viability of all this really comes down to economics. In theory, the resources floating up in space be the economic fuel necessary to take us to the stars. The Law of abundance may bring down the price of such commodities (including energy). Marsâ€“Earth trade may provide an economic rationale for continued settlement of the planet. This is possible because of breakthroughs happened in space and rocket science. The path to a human colony could be prepared by robotic systems. These systems locate resources, such as ground water or ice that would help a colony grow and thrive. Mars colonization is advocated by several non-governmental groups for a range of reasons and with varied proposals. One of the oldest groups is the Mars Society who promote a NASA program to accomplish human exploration of Mars.